Rediscovering the Classical: Graeco-Italian Relations and Ancient Drama in the early 20th Century. - Balaskas, Vasileios (My University, 2023)
During the early twentieth century, the connections formed among European intellectuals and institutions involved in performances of Graeco-Roman drama created international networks that included numerous classicists, archaeologists, writers, journalists, and artists. Until the mid-1910s, regular performances at archaeological sites inaugurated a more systematic engagement with classical heritage, especially in France, Italy, and Greece. On this basis, I argue that the Festival of Orange, the Festival of Syracuse, the Delphic Festivals, and other independent productions in the Mediterranean created powerful ideologies that linked classical heritage with modern collective identities. The relations among these intellectuals can shed light on the complex ways politics and aesthetic movements were intertwined in ways that reinvented the perception of classical antiquity in the first decades of the century.
Keywords: Teatro clásico; Grecia - Relaciones culturales - Roma; Festivales teatrales; Graeco-Italian relations; Delphic Festival; Ancient Drama